Naturalizations and the economic and social integration of immigrants - Mattias Engdahl (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2014)
I study the effects of naturalizations on labor market outcomes and family formation. The results show that naturalizations are associated with improving economic outcomes for immigrants from outside the OECD. The strength of the correlation varies depending on the country group and gender. A causal interpretation of the results is not possible as the outcomes start to improve already before the acquisition of citizenship. The study also shows that the propensity to get married rises for some country groups the years surrounding naturalizations. This is suggestive of naturalizations being related to not only labor market integration but also decisions regarding the family. Further, my findings illustrate that modeling assumptions are of great importance. Models that are not flexible enough could lead to false claims regarding causality.
Keywords: J13; J15; J21; J61; 330; naturalizations; labor market outcomes; family formation